Effects of supplementation of different enzymes in low energy diets for broilers - França, Thaisa Pereira de (2023)
Two experiments were conducted to evaluate the effects of different enzymes on the performance and gut morphology of broilers fed reduced energy diets, metabolizable energy values of reduced energy level diets. In experiment I - 1,280 male Cobb broilers, aged 1 to 42 days old, were used to evaluate performance parameters and gut morphology. Animals were distributed into 8 treatments with 8 replicates of 20 broilers each. The treatments consisted of: T1 - positive control (PC) diet with 3050 kcal ME/kg; T2 - negative control (NC) diet with a reduction of 200 kcal/kg; T3 - NC + Carbohydrase I (100 g/ton endo-1,4-beta-mannanase) ; T4 - NC + Carbohydrase II (100 g/ton endo-1,4-beta-xylanase and endo-1,4-beta-glucanase); T5 - NC + phytase (50 g/ton phytase-6); T6 - NC + Carbohydrase II + phytase; T7 - NC + Carbohydrase III (100g/ton endo-1,4-beta-xylanase); T8 - NC + Carbohydrase I + Carbohydrase II + phytase. The evaluated variables were body weight gain (BWG), feed intake (FI), feed conversion ratio (FCR), villus height (VH), crypt depth (CD), and villus height: crypt depth ratio (VH: CD). In experiment II – 420 14-day-old broilers were distributed into seven treatments with ten replicates of` six broilers each, to determine the apparent metabolizable energy (AME) and corrected for nitrogen balance (AMEn) of the diets. The same diets were used as treatments, excluding the PC. Comparing the treatments with the NC group, birds fed diets containing enzymes showed better BWG and FCR from 1 to 21 days old (P ≤ 0.05), and better FCR from 1 to 42 days (P ≤ 0.05). Additionally, the addition of Carbohydrase II and phytase promoted an increase in AME and AMEn of feed (P ≤ 0.05). Broilers fed with phytase showed higher VH when compared with the other treatments (P ≤ 0.05), whereas the treatments with phytase and Carbohydrases I, II, and phytase combination showed a better VH:CD (P ≤ 0.05). The inclusion of enzymes (carbohydrases and phytase) in broiler diets makes it possible to reduce feed energy levels without affecting performance parameters, AME corrected for nitrogen, and morphometry characteristics of the jejunum. Keywords: Broiler. Metabolizable Energy. Enzymes.